Optimal feeder routing and phase balancing for an unbalanced distribution system: a case study in Cambodia - Kay, Sopheak; Vai, Vannak; Eng, Samphors (International Journal of Applied Power Engineering (IJAPE), 2024)
This paper aims to minimize the distance of the feeder path from high-voltage/medium-voltage (HV/MV) substation to medium-voltage/low-voltage (MV/LV) transformers and minimize power loss in an unbalanced distribution system by the phase-swapping concept-based load balancing. The shortest path algorithm (SPA) and the genetic algorithm (GA) for optimal feeder routing and phase balancing separately in the MV unbalanced distribution network are proposed. First, the relevant data for the system is collected. These data include substation coordinates (X, Y), active and reactive power (P, Q), phase connections, and lines’ impedance (Z). secondly, the performance of the existing configuration of the test system with numerous indications is presented. Finally, the proposed method is performed to minimize the length and power losses. The real 47-bus test system in Cambodia is chosen to demonstrate the proposed method. In this study, overall power losses, the maximum voltage imbalance, and voltage regulation are computed by the backward/forward sweep load flow. The results based on the simulation indicate the importance of the proposed approach, especially for distribution system designers and operators.